Technological innovation in architecture and engineering education - an investigation on three generations from Turkey - Bayhan, Hasan Gokberk; Karaca, Ece (International Journal of Educational Technology in Higher Education, 2020)
The developments in technology have caused many radical changes in the curriculum of architecture and engineering (a/e) disciplines. At the same time, generations and their personal characteristics are in continuous change that is shaping newer education techniques. In this context, this study is aimed to compare the educational perceptions of generations X, Y and Z for the advancements in the curriculum. For this purpose, a literature review concerning the technological advancements in education and characteristics of X, Y, and Z generations are demonstrated. Then, a survey was conducted on 160 respondents to differ the perceptions between these generations while considering the respondents’ educational and social-related features. Results of this study support that Information Technology (IT)-related education is insufficient for the upcoming generations who were born and grew in the digital age. Generation Y is the least satisfied with IT-related lectures and more affected by the movement of sustainability. The perceptions between the generations are found statistically different and solutions are offered for the upcoming generations. The outcomes of this study are expected to guide professionals in a/e education to better fulfill the expectations of the upcoming generations.